DIGITAL TRANSFORMATION AND PUBLIC VALUE CREATION IN PUBLIC ADMINISTRATION: A SYSTEMATIC LITERATURE REVIEW ON CO-PRODUCTION-BASED GOVERNANCE - Nur Budiyanto, Muhammad; Putra, Raniasa; Lionardo, Andries; Eko Aryansyah, Januar; Syafebri, Arrahman (Indonesian Association for Public Administration (IAPA), 2025)
Digital transformation in public administration has become a global imperative to enhance efficiency, transparency, and citizen participation in governance. This study explores how digital transformation and co-production contribute to multidimensional public value creation through a systematic literature review of 35 peer-reviewed articles published between 2020 and 2024. Following the PRISMA 2020 protocol, the research systematically identified, screened, and analyzed relevant studies indexed in Scopus, Web of Science, and ScienceDirect. The analysis, visualized using VOSviewer version 1.6.20, identified four primary public value dimensions: administrative efficiency, citizen engagement, social equity, and economic optimization. Co-production emerges as a crucial mechanism linking digital transformation to these outcomes, though institutional capacity, digital literacy, and governance culture strongly moderate the results. The study highlights that sustainable digital transformation in public administration requires not only technological innovation but also active citizen participation and adaptive governance structures. Theoretically, this work reinforces the Public Value Management framework, while practically, it offers insights for policymakers to design inclusive, transparent, and citizen-centered digital service reforms.